Input energy measurement toward warm dense matter generation using intense pulsed power generator. (May 2016) - Hayashi, R; Ito, T; Ishitani, T; Tamura, F; Kudo, T; Takakura, N; Kashine, K; Takahashi, K; Sasaki, T; Kikuchi, T; Harada, Nob.; Jiang, W; et al.
Abstract: In order to investigate properties of warm dense matter (WDM) in inertial confinement fusion (ICF), evaluation method for the WDM with isochoric heating on the implosion time-scale using an intense pulsed power generator ETIGO-II (∼1 TW, ∼50 ns) has been considered. In this study, the history of input energy into the sample is measured from the voltage and the current waveforms. To achieve isochoric heating, a foamed aluminum with pore sizes 600 μ m and with 90% porosity was packed into a hollow glass capillary (ø 5 mm × 10 mm). The temperature of the sample is calculated from the numerical calculation using the measured input power. According to the above measurements, the input energy into a sample and the achievable temperature are estimated to be 300 J and 6000 K. It indicates that the WDM state is generated using the proposed method with ICF implosion time-scale.